PENGEMBANGAN MODUL MATEMATIKA MATERI HUBUNGAN ANTAR SUDUT PADA DUA GARIS SEJAJAR - Permata Nugrahani; Maria Suci Apriani (Jurnal Pendidikan Matematika Undiksha, 2021)
This study aims to determine the quality of the module that are considered from material and media aspects and to know students' responses at the product trial stage. This research was Research and Development (R&D). To find out the quality of the module, that was looked from the validity, we used expert judgment from three Mathematics Education lecturers. Meanwhile, to find out the students' responses, we conducted a trial on 32 students of Class VII F, SMP Regina Pacis Surakarta. The results of this study are the quality of the mathematical module that has been designed in terms of material the results are very good with an average of 3.29 and need to add exercises to accommodate the questions of cognitive demands analyzing or creating. The quality of the mathematics module in terms of media is very good with an average of 3.33 and it is necessary to add exercises about HOTS. Students respond very well to the mathematics module that is designed with an average of 3.39 and accept this module to help students learn independently outside the learning process in class